Between the Extremes: A JWST Spectroscopic Benchmark for High-redshift Galaxies Using ∼500 Confirmed Sources at z ≥ 5 - Guido Roberts-Borsani; Tommaso Treu; Alice Shapley; Adriano Fontana; Laura Pentericci; Marco Castellano; Takahiro Morishita; Pietro Bergamini; Piero Rosati (The Astrophysical Journal)
The exceptional spectra of the most luminous z > 10 sources observed so far have challenged our understanding of early galaxy evolution, requiring a new observational benchmark for meaningful interpretation. As such, we construct spectroscopic templates representative of high-redshift, star-forming populations, using 482 confirmed sources at z = 5.0−12.9 with JWST/NIRSpec prism observations, and report on their average properties. We find z = 5−11 galaxies are dominated by blue UV continuum slopes ( β = −2.3 to −2.7) and reduced Balmer indices, characteristic of dust-poor and young systems, with a shift towards bluer slopes and younger ages with redshift. The evolution is mirrored by ubiquitous C iii ] detections across all redshifts (rest-frame equivalent widths of 5−14 Å), which increase in strength towards early times. Rest-frame optical lines reveal elevated ratios (O32 = 7–31, R23 = 5–8, and Ne3O2 = 1−2) and subsolar metallicities (log(O/H) = 7.3−7.9), typical of ionization conditions and metallicities rarely observed in z ∼ 0 populations. Within our sample, we identify 57 Ly α emitters, which we stack and compare to a matched sample of nonemitters. The former are characterized by more extreme ionizing conditions with enhanced C iii ], C iv , and He ii + [O iii ] line emission, younger stellar populations from Balmer jumps, and a more pristine interstellar medium seen through bluer UV slopes and elevated rest-frame optical line ratios. The novel comparison illustrates important intrinsic differences between the two populations, with implications for Ly α visibility. The spectral templates derived here represent a new observational benchmark with which to interpret high-redshift sources, lifting our constraints on their global properties to unprecedented heights and extending out to the earliest of cosmic times.